2015
DOI: 10.1371/journal.pone.0122031
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Epidemiology and Risk Factors of Acute Coronary Syndrome in Chinese Patients with Type 2 Diabetes: A Long-Term Prospective Cohort Study

Abstract: ObjectiveDiabetic patients with acute coronary syndrome (ACS) are at higher risk of poor outcome than are non-diabetic patients with ACS. Few studies have focused on sex-related ACS incidence, ACS-related mortality or risk factors to affects sex specific ACS in Chinese with Type 2 diabetes mellitus (T2DM). Based on a hospital-based cohort of Chinese patients with T2DM, we aimed to investigate whether there was sex difference in ACS or ACS-related mortality or risk factors of ACS.MethodsTotally 2,135 Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
2
20
1
3
Order By: Relevance
“…Scientific research conducted over the years into predictive factors for AMI have shown that age and gender are two of the main predictors [7][8][9][10]. In their study into demographic risk factors related to the occurrence of myocardial infarction, Duan et al [7] showed that myocardial infarction is more prevalent among men than women, and that this risk increases considerably above the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific research conducted over the years into predictive factors for AMI have shown that age and gender are two of the main predictors [7][8][9][10]. In their study into demographic risk factors related to the occurrence of myocardial infarction, Duan et al [7] showed that myocardial infarction is more prevalent among men than women, and that this risk increases considerably above the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of DM is expected to increase from 4% in 1995 to 5.4% by the year 2025 [ 20 ], and that number of patients will reach 642 million by 2040 [ 21 ]. Currently, the countries with the largest number of diabetic patients are India, China, and United States [ 22 ]. Inspiringly, the morbidity and mortality caused by DM can be reduced by regular screening, early detection, and appropriate treatment of chronic complications [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional risk factors of CHD include age, hypertension, DM, hyperlipidemia, and smoking [24], and as a major risk factor, DM has been widely concerned by many scholars. Studies have shown that long-term hyperglycemia leads to increased vascular endothelial permeability, abnormal expression of inflammatory factors, and thus causes the body to be in a state of high inflammatory response [25]. In addition, the hyperglycemia leads to excessive production of reactive oxygen species and decreases the activity of antioxidant enzymes, and thus causes the body to be in a state of oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%